Finding balance between work and play - Forsgren, Nicole; Ceccarelli, Greg; Jedamski, Derek; Kelly, Scot; Sullivan, Clair (The State of the Octoverse, 2020)
Over the past year, many developers and other technology professionals have transitioned to a remote-first world, as COVID-19 pressed organizations to support working from home whenever possible. This shift quickly changed the routines and environments where we work and learn, redrawing the lines between personal and professional lives. How does this affect the ways we develop and deliver software, both at work and in our open source projects?